In Peri-urban Aligarh... Blooming floriculture for prosperity - Khan, Nizamuddin; Salman, Mohd. Sadiq; Rehaman, Md Akhter Haninur (Indian Horticulture, 2019)
The peri-urban area of Aligarh city in north India has witnessed a tremendous growth of floriculture over the last decade. Caste-specific domination, small-scale production by marginal and small farmers and inefficient marketing at local level hampers the growth of floriculture in the region. Efficient marketing practices, government support and production at commercial scale are needed to develop floriculture and ensure better returns to farmers.